Legalitas Perkawinan Beda Agama: Mengungkap Disparitas Putusan Pengadilan di Indonesia - Ayub Mursalin (Fakultas Hukum Universitas Jambi, 2023)
In Indonesian society, interfaith marriages always spark controversy. Due to this fact, some people who are planning or have already begun an interfaith marriage turn to the court to ask for the legalization of their marriage. Through a doctrinal analysis using a comparative law approach, this article aims to examine the arguments of judges in adjudicating and deciding on the legality of interfaith marriages in three court institutions: the Primary Court, the Supreme Court, and the Constitutional Court. Even though the three court institutions have distinct absolute competencies, it is vital to analyze them to identify any inconsistencies or harmonies in the legal arguments, as this would have a significant impact on views and even access to public law in the case. This paper argues that, on the one hand, there is a legal conflict between the factors considered in the Supreme Court's judgment and those considered in the Primary Court's decision in situations involving interfaith marriages. While the Supreme Court, which initially permitted interfaith marriages, now tends to forbid them, the Primary Court's reasoning generally tends to support interfaith marriages. The Constitutional Court's ruling in 2015 regarding the judicial review of the Marriage Law of 1974 against the Constitution of 1945, which in essence forbids interfaith marriage but does not violate the right to establish a family, appears to have caused a change in the justification for the Supreme Court's decision. Abstrak Legalitas perkawinan beda agama di Indonesia masih terus menjadi polemik di tengah masyarakat. Fakta ini menyebabkan sebagian mereka yang akan atau telah melangsungkan perkawinan beda agama untuk meminta pengadilan sebagai forum yang bisa mengesahkan perkawinannya. Melalui kajian doktrinal dengan pendekatan perbandingan hukum, artikel ini akan mengungkap argumen hakim dalam mengadili dan memutus legalitas perkawinan beda agama pada tiga lembaga pengadilan yang berbeda, yaitu Pengadilan Negeri, Mahkamah Agung, dan Mahkamah Konstitusi. Meski ketiga lembaga pengadilan tersebut memiliki kompetensi absolut yang berbeda, kajian terhadapnya menjadi penting dalam upaya menemukan keselarasan atau ketidakselarasan argumentasi hukum, dan ini akan sangat menentukan sikap dan bahkan akses hukum masyarakat dalam perkara tersebut. Hasil kajian menunjukkan adanya ketidakselarasan logika hukum antara putusan-putusan Pengadilan Negeri dan Mahkamah Agung maupun Mahkamah Konstitusi terhadap perkara legalitas perkawinan beda agama yang diajukan para pemohon. Putusan-putusan Pengadilan Negeri pada umumnya cenderung membolehkan perkawinan beda agama, sedangkan Mahkamah Agung, yang awalnya membolehkan perkawinan beda agama, sekarang memiliki kecenderungan untuk melarangnya. Pergeseran kecenderungan Putusan Mahkamah Agung ini baru terjadi pasca-putusan Mahkamah Konstitusi tentang uji materiil Undang-Undang Perkawinan 1974 terhadap Undang-Undang Dasar 1945 di tahun 2015 yang pada intinya pelarangan perkawinan beda agama tidak melanggar hak asasi manusia untuk membangun sebuah rumah tangga.